HPV E6/E7 mRNA In Situ Hybridization in the Diagnosis of Cervical Low-grade Squamous Intraepithelial Lesions (LSIL). (February 2018) - Mills, Anne M.; Coppock, Joseph D.; Willis, Brian C.; Stoler, Mark H.
Abstract : Cervical low-grade squamous intraepithelial lesions (LSIL) (aka cervical intraepithelial neoplasia, grade 1 [CIN1]) can present considerable diagnostic challenges and are associated with poor interobserver reproducibility and overdiagnosis. Furthermore, ancillary studies such as p16 immunohistochemistry have shown little utility in resolving the LSIL versus negative/reactive differential. Human papillomavirus (HPV) RNA in situ hybridization (ISH) has shown promise as a diagnostic aid in this setting, but has not been studied in a large case series. We herein investigate high-risk and low-risk HPV RNA ISH in 126 cervical biopsies originally diagnosed as LSIL/CIN1 and compare HPV RNA ISH results to expert-adjudicated morphologic diagnosis to assess whether this assay can help routine cases attain the existing "gold standard" of morphologic consensus diagnosis. We also assess whether this criterion standard can be further improved by integration of HPV RNA ISH results. A consensus diagnosis of intraepithelial lesion (CIN1 + ) was confirmed in 61% of cases, whereas 57% were HPV RNA + . HPV-RNA positivity was 84% sensitive and 86% specific for an expert-adjudicated diagnosis of CIN1 + . Conversely, consensus diagnosis was 90% sensitive and 78% specific for the presence of HPV RNA. Integrating RNA ISH into morphologic review led to further reclassification of 10% of cases, resulting in 95% sensitivity and 98% specificity of HPV RNA ISH for a CIN1 + diagnosis and 98% sensitivity and 92% specificity of CIN1 + for the presence of HPV RNA. These findings suggest that judicious use of HPV RNA ISH can improve the accuracy of LSIL/CIN1 diagnosis for morphologically ambiguous cases.